ANALISIS RELEVANSI NILAI-NILAI MORAL RITUAL SEKUJANG SUKU SERAWAI DALAM PEMBELAJARAN PPKN TEMATIK TERPADU SISWA KELAS V SDN 81 SELUMA - Ady Darmansyah; Puspa Djuwita; Abdul Muktadir (Universitas Bengkulu, 2022)
This study discusses the moral values of the Sekujang ritual of Serawai Tribe integrated in learning civic education for fifth grade elementary school students of 81 Seluma. The goal to be achieved is to describe the moral values in the Serawai tribe's Sekujang ritual which can be internalized in learning civic education for fifth grade students of the 81 Seluma elementary school. This research is a qualitative descriptive study with an ethnographic approach. The results showed that the class V teachers in the 81 Seluma elementary school could understand and interpret the ritual of the Sekujang tribe of Serawai, the thematic learning design of the civic education learning content on Theme 8 Sub-theme 2 Learning 3, internalization of Sekujang moral values in the civic education learning design for fifth grade students of 81 Seluma elementary school, and the Sekujang moral values evaluation design in the learning of civic education for fifth grade students of the 81 Seluma elementary school which was made by the teacher was not fully optimal. There has been an internalization of moral values in the design of civic education learning, but it has not been programmed and there is the relevance of the Sekujang ritual moral values in civic education learning. Keywords : Moral Values, Sekujang Rituals and Civic Education Learning